The facilitation of critical thinking in a Technology Education classroom - Piet Ankiewicz; Fatima Adam; Estelle de Swardt; Elna Gross (Acta Academica, 2001)
The teacher’s role in facilitating learning and thinking in Technology Education classrooms is crucial to creating an environment conducive to the promotion and development of thinking. The aim of this study was to   determine how teacher facilitation can promote and develop thinking in Technology Education lessons. A single case study using a qualitative research approach with convenience sampling and involving grade eight Technology Education learners was used to conduct the study. Data collection was by means of direct non-participant observation of both teacher-learner and learnerlearner interaction. Transcripts of video tapes, audio tapes, field notes and   instructional aids were analysed and recommendations for the facilitation of co-operative learning and critical thinking in the Technology Education classroom were made.